Carbon fiber-promoted activation of catalyst for efficient growth of single-walled carbon nanotubes. (January 2020) - Xin, Benwu; Gao, Wenke; Ji, Zhonghai; Zhang, Shuchen; Xin, Liantao; Zhao, Lifen; Xue, Han; Wu, Qianru; Zhang, Lili; Liu, Chang; Zhang, Jin; He, Maoshuai
Abstract: Carbon fibers are placed onto substrate surface with dispersed Co particles to promote the growth efficiency of single-walled carbon nanotubes (SWNTs). During chemical vapor deposition (CVD) process, micro-spaces are fabricated between the carbon fibers and the substrate surface, which modify the Knudsen number of CO and increase its efficient contact with cobalt oxide nanoparticles, enhancing the reduction of catalysts and the nucleation of SWNTs. Compared with surface grown SWNTs without covering carbon fibers, SWNTs grown under carbon fibers demonstrate a much higher catalyst efficiency, i.e. a SWNT density as high as ∼140 SWNTs/ μ m 2 . X-ray photoelectron spectroscopy characterizations confirm that the presence of carbon fibers promotes the reduction of cobalt oxide catalyst particles and carbon dissolution inside catalyst particles, which are crucial for catalyst activation and subsequent SWNT nucleation. This work provides a new strategy for the efficient growth of SWNTs, which benefits high-density growth of SWNTs required for future nanoelectronics applications. Graphical abstract: Micro-space generated by placing carbon fibers on top of supported catalyst particles promotes the reduction of catalyst and the carbon cap "lift off", resulting in the efficient growth of single-walled carbon nanotubes by chemical vapor deposition. Image 1